(untitled) (International Journal of Engineering and Computer Science, 2018)
- It is not easy to quantify the large amount of data stored electronically. Data is in the unit of zettabytes or exabytes referred as Big Data. Hadoop system is used to process large datasets. Map Reduce program is used to collect data according to the request. To process big data proper scheduling is required to achieve greater performance. Scheduling is a technique of assigning jobs to available resources in a manner to minimize starvation and maximize resource utilization. Performance of scheduling technique can be improved by applying deadline constraints on jobs. The objective is to study Map Reduce and different scheduling algorithms that can be used to achieve better performance.